Dietary supplementation of garlic (Allium sativum) modulates gut microbiota and health status of tilapia (Oreochromis niloticus) against Streptococcus iniae infection. (10th May 2019) - Foysal, Md Javed; Alam, Mahbubul; Momtaz, Farhana; Chaklader, Md Reaz; Siddik, Muhammad A. B.; Cole, Anthony; Fotedar, Ravi; Rahman, Md Mahbubur
Abstract: This study was conducted to characterize the causative agent of streptococcosis in tilapia ( Oreochromis niloticus ) and control of Streptococcus infection by means of garlic ( Allium sativum ) supplementation. The morphological, biochemical and polymerase chain reaction amplification confirmed 11 isolates belong to Streptococcus iniae from the infected fish eyes and tissue samples. Random screening of 12 well‐known medicinal plant parts against S. iniae revealed the garlic extract as the most effective herbal recovery against Streptococcus infection. In vivo challenge test with dietary supplementation of garlic powder significantly improved survival rates of fish against S. iniae infections, and modulate the microbial community and cytokine gene expression profiling in the intestine of the experimental tilapia. Among the two garlic supplemented treatments, 1.0 g garlic supplemented diet significantly increased ( p < 0.05) the survival rates of tilapia and the gut bacterial operational transitional units abundance for Proteobacteria and Tenericutes, the phyla associated with healthy intestinal flora. The bacterial diversity index also found high with garlic supplemented diets. Significant upregulations of IL‐10 and IL‐17F gene expression in the intestinal tissue were observed with 1.0 g garlic supplemented diet where IL‐8 and IL‐1β expression levels were relatively static. The dietary supplementation of garlic, therefore, could be effective in the prevention of S. iniae infection in fish.